Spices laid out for drying in the courtyard of an East Indian residence - Mumbai Archive Project Team (Jio Institute, 2024)
Spices are laid out for drying in the courtyard of Marthahil, a heritage home at Vasai that has been the residence of an East Indian family for more than 150 years. The masala-making season usually lasts from March until May. Earlier, drying spices in the open was a common sight in East Indian neighbourhoods, though the practice is declining as people nowadays opt to buy masala from the market.